Adherence and acceptance of a home-based telemonitoring application used by multi-morbid patients aged 65 years and older. (January 2022) - Lang, Caroline; Voigt, Karen; Neumann, Robert; Bergmann, Antje; Holthoff-Detto, Vjera
Introduction: Currently, there are only a small number of comprehensive study results on adherence and acceptance of telemonitoring applications (TMAs) regarding multi-morbid older patients. The ATMoSPHAERE study aimed to develop an information and communication platform for an intersectoral networking of, for example, general practitioners, therapists, social services and the multi-morbid older patient. Methods: The study presented was designed as a longitudinal bicentric intervention study which focused on multi-morbid patients aged ≥65 years using home-based telemedical measurement and input devices. The development and testing of this TMA aimed to optimise patients' health care through intersectoral networking of all treating actors. Quantitative methods of data collection and analysis were used. Results: Patients who completed the study were significantly younger than drop-outs and non-participants. The mental health of study patients significantly improved between the beginning and end of TMA use. The main reason for non-participation in the study was the high time expenditure when participating in the study. No perceived (information) benefits for health and insufficient content variety were the main reasons for drop-out. Appropriateness and handling of TMAs must be aligned with the needs of the heterogeneous user group of multi-morbid patients in order to increase acceptance and the added value of TMAs. Telemonitoring hardware should be oriented on functional capabilities of the older target group. Telemonitoring software content requires an individual, disease-specific approach for patients. The TMA should be unobtrusively integrated into usual daily life and be used to an appropriate extent according to the underlying disease in order to avoid stressing patients. With regard to adherence concerning TMAs, it is crucial to provide a contact person who is always available for patients having problems handling TMAs. Health concerns and questions can thus be addressed early, providing a feeling of safety in the care process. Discussion: User acceptance of TMAs is an essential indicator and driver for use and for future implementation efforts in health care. In order to achieve maximum user centricity in development processes, patients must be involved as experts, co-designers and future users, considering their needs and perceptions.